Design and Implementation of IoT Based WSN Smart Home Automation Intelligent System using Flask Web Server - G. Mallikharjuna Rao (New Approaches in Engineering Research Vol. 11, 2021)
The smart home is changing the way we live today. In this project, we introduce to automate the entire home appliances using a wireless sensor network to control and monitor the connectivity and communication using Raspberry Pi. The Raspberry Pi is used as central coordinator to connect with four NodeMCU wirelessly operating under star network topology to handle the home appliances. The Raspberry Pi and NodeMCU modules are connected to the internet using the hotspot. The coordinator node will monitor and control the process through the HTTP web page protocol. The web page was developed using HTML, CSS, JavaScript, and chart.js, and the hosted website is on the Flask web server. The webpage automation system will control the home appliances through the Wi-Fi module; it makes a complete setup of home automation using the Internet of Things. Finally, the entire core design of hardware and software to manage the home appliances through a Flask web server is done in local storage and can be viewed in a web browser using the client-server model.